Biochemical and morphological properties of Hepatitis C virus particles and determination of their lipidome - Merz, Andreas; Long, Gang; Hiet, Marie-Sophie; Brügger, Britta; Chlanda, Petr; Andre, Patrice; Wieland, Felix T.; Krijnse-Locker, Jacomine; Bartenschlager, Ralf (The journal of biological chemistry, 2011)
A hallmark of hepatitis C virus (HCV) particles is their association with host cell lipids, most notably lipoprotein components. It is thought that this property accounts for the low density of virus particles and their large heterogeneity. However, the composition of infectious virions and their biochemical and morphological properties are largely unknown. We developed a system in which the envelope glycoprotein E2 was N-terminally tagged with a FLAG epitope. This virus, designated Jc1E2FLAG, produced infectivity titers to wild type levels and allowed affinity purification of virus particles that were analyzed for their protein and lipid composition. By using mass spectrometry, we found the lipid composition of Jc1E2FLAG particles to resemble the one very low- and low density-lipoprotein with cholesteryl esters accounting for almost half of the total HCV lipids. Thus, HCV particles possess a unique lipid composition that is very distinct from all other viruses analyzed so far and from the human liver cells in which HCV was produced. By electron microscopy (EM), we found purified Jc1E2FLAG particles to be heterogeneous, mostly spherical structures, with an average diameter of about 73 nm. Importantly, the majority of E2-containing particles also contained apoE on their surface as assessed by immuno-EM. Taken together, we describe a rapid and efficient system for the production of large quantities of affinity-purified HCV allowing a comprehensive analysis of the infectious virion, including the determination of its lipid composition.
Elektronische Reproduktion der Druckausgabe
Gesehen am 18.08.2022